Rethinking Representation: Representative Claims in Global Perspective - Guasti, Petra (2019)
The established notion of political representation is challenged on multiple accounts—theoretically, conceptually, and empirically. The contributions to this thematic issue explore the constructivist turn as the means for rethinking political representation today around the world. The articles included here seek to reconsider representation by theoretically and empirically reassessing how representation is conceptualized, claimed and performed—in Western and non-Western contexts. In recognition that democratic representation in Western countries is in a process of fundamental transformation and that non-Western countries no longer aim at replicating established Western models, we look for representation around the world—specifically in: Belgium, Brazil, France, Germany, China, and India. This enables us to advance the study of representative democracy from a global perspective. We show the limits and gaps in the constructivist literature and the benefits of theory-driven empirical research. Finally, we provide conceptual tools and frameworks for the (comparative) study of claims of representation.